Efficacy of weekly teriparatide does not vary by baseline fracture probability calculated using FRAX - Harvey, N. C. (Osteoporos Int, 2015)
SUMMARY: The aim of this study was to determine the efficacy of once-weekly teriparatide as a function of baseline fracture risk. Treatment with once-weekly teriparatide was associated with a statistically significant 79 % decrease in vertebral fractures, and in the cohort as a whole, efficacy was not related to baseline fracture risk. INTRODUCTION: Previous studies have suggested that the efficacy of some interventions may be greater in the segment of the population at highest fracture risk as assessed by the FRAX® algorithms. The aim of the present study was to determine whether the antifracture efficacy of weekly teriparatide was dependent on the magnitude of fracture risk. METHODS: Baseline fracture probabilities (using FRAX) were computed from the primary data of a phase 3 study (TOWER) of the effects of weekly teriparatide in 542 men and postmenopausal women with osteoporosis. The outcome variable comprised morphometric vertebral fractures. Interactions between fracture probability and efficacy were explored by Poisson regression. RESULTS: The 10-year probability of major osteoporotic fractures (without BMD) ranged from 7.2 to 42.2 %. FRAX-based hip fracture probabilities ranged from 0.9 to 29.3 %. Treatment with teriparatide was associated with a 79 % (95 % CI 52–91 %) decrease in vertebral fractures assessed by semiquantitative morphometry. Relative risk reductions for the effect of teriparatide on the fracture outcome did not change significantly across the range of fracture probabilities (p = 0.28). In a subgroup analysis of 346 (64 %) participants who had FRAX probabilities calculated with the inclusion of BMD, there was a small but significant interaction (p = 0.028) between efficacy and baseline fracture probability such that high fracture probabilities were associated with lower efficacy. CONCLUSION: Weekly teriparatide significantly decreased the risk of morphometric vertebral fractures in men and postmenopausal women with osteoporosis. Overall, the efficacy of teriparatide was not dependent on the level of fracture risk assessed by FRAX in the cohort as a whole.